Os arranjos produtivos locais e o processo de coordenação intergovernamental: o papel dos governos dos estados como articuladores de políticas públicas - Sydow, Cristina Toth (2012)
One of the big issues of the Brazilian Federalism is the role of the states in the field of public policies. If, on the one hand, this role in welfare-State systems is still facing a lack of definitions and the literature on aspects such as participation in the design and execution of policies in the fields of health, education, social assistance and housing is quite restricted, the current scene seems to be, on the other, quite different in regard to the policies of economic development, as the states count with a significant advantage vis-à-vis the municipalities and the federal government. This thesis is an attempt to show that the role of the states has expanded and has become more specialized in the functions connected to infrastructure and regional development. Through the works of analysis and planning, and with their capacity of linking through several actors of their development agencies and secretariats of economic development, the states can display a privileged view of their particularities and similarities in the productive and logistical activities, and of their specific needs. States are also taking up a variety of actions in the design, execution and implementation of policies that involve linkages with the other members of the Federation, with the private sector and the civil society, and they are furthering new socio-institutional architectures in the creation, development and maintenance of support instruments. Such institutional environment enables the study of the mechanisms of territorial associationism, and, particularly, the Local Productive Arrangements, which have been increasingly used as instruments of regional development by the states, with the support of the federal government. The Local Productive Arrangements have an associationist and voluntary nature, and they are instruments that can be employed and improved by the states, as the territorial basis on which they find themselves have a pre-existing productive vocation, and as the interventions towards stimulating, building capacities and professional training are among the possibilities of action by the states. From this premise, the present work analyzes the role that has been played by the states in the design, execution and articulation of policies for Local Productive Arrangements. Based on the assumption that the states do count with a better institutional structure than the municipalities and the federal government for specific policies that favor the Local Productive Arrangements, it seeks to understand how the three analyzed states – Pernambuco, Minas Gerais and Rio Grande do Sul – have dealt with the issue.